Development of the shape of the cam profile of mechanical yam vibrator using cycloid motion - Osanyinpeju, Kifilideen; Aderinlewo, Adewole A.; Dairo, Olawale U.; Adetunji, Olayide R.; Ajisegiri, Emmanuel S.A. (Sustainable Engineering and Innovation, 2022)
At a high frequency of vibration; the cam of a vibrator always encounters the issue of jamming or the follower rolling off or losing contact with the cam when the appropriate design is not carried out. This study, therefore, developed the shape of the cam profile of mechanical yam vibrator using cycloid motion in the South. Displacement equations from the base circle to the cam profile were developed to obtain the shape of the cam using cycloid motion. A vibrometer was used to evaluate the developed 5 mm, 10 mm, and 20 mm cam sizes installed in a mechanical yam vibrator. The maximum displacement recorded for 5 mm, 10 mm and 20 mm cam sizes were 4.47 mm, 8.71 mm, and 14.54 mm respectively for low (1 – 5 Hz) frequency; 4.58 mm, 8.84 mm and 16.34 mm respectively for medium (60 – 100 Hz) frequency; and 4.66 mm, 9.09 mm and 17.30 mm respectively for high (150 – 200 Hz) frequency. This study shows that a cycloid cam would operate smoothly at low, medium, and high frequencies of vibration and function properly for frequency and displacement of vibration up to 200 Hz and 20 mm respectively without jamming and failing. A cycloid cam is therefore recommended for low, medium, and high frequencies motion of vibration.